Survey of Dribbling and Shooting Skills of Futsal Games at State Elementary School 02 Seberang Musi Kepahiang Regency - Mustopa, David Hidayatullah; Mesterion, Mesterion; Martiani, Martiani (Journal of Physical Education and Sports, 2024)
This study aims to determine the level of dribbling and shooting skills of futsal players at State Elementary School 02 Kepahiang Regency. This research method is survey research with a quantitative descriptive approach where researchers only see how the Dribbling Level of Futsal players. The results showed that a total of 4 people (10%) had a very poor category. A total of 13 people (32.5%) have a less category. A total of 18 people (45%) have a moderate category. A total of 5 people (12.5%) have a good category. The conclusion that the dribbling and shooting skills of futsal games at State Elementary School 02 Kepahiang Regency in this study show the classification of "good" to "very less".